Gender Differences in Request Strategies among Graduate Students - Tiwari, Hari Prasad (International Research Journal of MMC, 2024)
Proficiency in request strategies is key in handling social hierarchies and managing interpersonal communication. It is also essential in reducing misunderstandings and enhancing communication efficiency in both educational and professional settings. This quantitative survey investigated the request strategies employed by graduate students in different hierarchical contexts. The sample population consisted of 100 B.Ed. (Bachelor of Education) major English students from ten campuses affiliated to Tribhuvan University (TU). The sample was selected employing stratified simple random sampling method. The data were collected using a structured questionnaire with nine closed-ended questions in the year 2081 BS. The data were analyzed using descriptive statistics technique of quantitative data analysis. The result revealed distinct patterns in request strategies when addressing individuals of varying ranks. In higher-to-lower rank scenarios, male respondents predominantly used mood derivable strategies, while females showed a preference for performatives and hedge performatives. For equal-to-equal rank situations, males favored direct mood derivable strategies, while females used a more varied approach with higher incidences of indirect strategies. In lower-to-higher rank contexts, males again showed a preference for direct approaches, whereas females exhibited a higher use of indirect and polite strategies. These findings highlight significant gender-based differences in communication strategies which emphasize the need for personalized approaches in educational and professional settings.